Multicriteria Evaluation Framework for Industrial Heritage Adaptive Reuse: The Role of the ‘Intrinsic Value’ - Francesca Nocca; Martina Bosone; Manuel Orabona (Land, 2024)
At the end of the 20th century, most industrial cities faced a massive phase of de-industrialisation, resulting in abandoned areas. However, these areas, rich in history and heritage, can represent significant resources for the regeneration of entire territories. Adaptive Reuse (AR) is one of the most appropriate strategies for the sustainable regeneration of brownfield sites: it gives new life to a ‘dead’ land, extending its use value so that it can continue to be enjoyed both by present and future generations. Decision-making processes concerning Industrial Heritage Adaptive Reuse (IHAR) cannot ignore the role that ‘intrinsic value’ plays in orienting development choices in such areas. Adopting participatory decision-making processes enables the inclusion of different values and interests of the stakeholders and, at the same time, increasing their awareness about the decision-making problem, thus reducing conflicts. This contribution intends to propose an evaluation framework to assess the multidimensional impacts of IHAR, considering the different values characterising them, and to support decision-making processes for the identification of the ‘preferable’ transformation scenario. This evaluation framework is applied, through the use of the TOPSIS multi-criteria evaluation method, in the case study of the ex-Italsider area in Bagnoli district (Naples, Italy), an industrial steel plant decommissioned in the early 1990s.